Necessidades de cuidado em educação em saúde de estudantes adolescentes na ótica de professores - (:unkn) unknown (Universidade Federal do Pampa, 2015)
The adolescent health has long been an area overlooked by professionals and health institutions for not recognizing that teens have their own characteristics and undergo many transformations. Health education forms a set of knowledge and practices whose principle disease prevention and health promotion. Health school, health education shows up an important strategy to be held in the school, because it has a comprehensive and multidisciplinary vision of the human being, which considers people in their family, community, social and environmental context. Thus, health promotion develops knowledge, skills and abilities for self-care of health and the prevention of risk behaviors and take you an analysis of the values, attitudes, social conditions and the lifestyles of those involved subjects themselves. Thus, it seeks to identify the care demands in health education for adolescent students from the perspective of educators already studied. This is a literature integrative review to answer the question: What are the care needs in health education of adolescents are identified by teachers? Literature search was conducted in LILCAS databases BDENF and SCIELO to identify articles published from 2005 to 2015. The descriptors used were school health and teaching. Studies were included with full text available in Portuguese. Theses were excluded, dissertations, monographs and books. The results allowed the identification of two categories that reflect care needs in the perception of teachers, which were: Health needs as perceived by teachers; difficulties faced by teachers in implementing health education interventions with adolescents. Allowing to identify the themes identified by teachers and described in the literature, among which stood out sexuality, alcohol and drugs. Concluding so that teachers do not feel prepared to address health education in school in order to prevent possible health disorders in adolescents.
Care needs in health education of adolescent students from the perspective of teachers
Keywords: Enfermagem; Educação em saúde; Adolescent health; Nursing; Health education; Saúde do adolescente; CNPQ::CIENCIAS DA SAUDE